Musical forces: Motion, Metaphor, and Meaning in Music - Larson, Steve 1955-2011; Hatten, Robert S. (Bloomington Indiana University Press, 2012)
Steve Larson drew on his 20 years of research in music theory, cognitive linguistics, experimental psychology, and artificial intelligenceas well as his skill as a jazz pianistto show how the experience of physical motion can shape ones musical experience. Clarifying the roles of analogy, metaphor, grouping, pattern, hierarchy, and emergence in the explanation of musical meaning, Larson explained how listeners hear tonal music through the analogues of physical gravity, magnetism, and inertia. His theory of melodic expectation goes beyond prior theories in predicting complete melodic patterns. Larson elegantly demonstrated how rhythm and meter arise from, and are given meaning by, these same musical forces.
Keywords: Music philosophy and esthetics; Music theory; Science